2018
DOI: 10.1186/s13104-018-3906-4
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Brucella abortus antibodies among women with spontaneous abortion in the city of Mwanza: unrecognized link or coincidence?

Abstract: ObjectiveThis study investigated the association of Brucella seropositivity and spontaneous abortions in human population in the city of Mwanza, Tanzania.ResultsA comparative cross sectional study which used 148 sera from women with spontaneous abortion and 250 sera from full-term delivered women was conducted in July 2017. Detection of Brucella abortus and Brucella melitensis antibodies was done using slide agglutination test. Data were analyzed using STATA version 13 software. The median age of the study par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Our results are similar to those reported in Jordan (Abo‐shehada & Abu‐Halaweh, ). However, a study reported differences between brucellosis prevalence in miscarriage and non‐miscarriage cases in Mwanza‐Tanzania (Mujuni et al, ). In this study, there was a high association between the exposure and the positivity to brucellosis (OR = 19; 95% CI = 1.8–203).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are similar to those reported in Jordan (Abo‐shehada & Abu‐Halaweh, ). However, a study reported differences between brucellosis prevalence in miscarriage and non‐miscarriage cases in Mwanza‐Tanzania (Mujuni et al, ). In this study, there was a high association between the exposure and the positivity to brucellosis (OR = 19; 95% CI = 1.8–203).…”
Section: Discussionmentioning
confidence: 99%
“…Although suspected, since the initial report of abortion of a farmer's wife in the 1900s (Eyre, ), pregnancy complications in infected women have long been underestimated. However, it is now recognised, with a growing number of epidemiological studies describing increased risks of adverse obstetric outcomes (preterm delivery, spontaneous abortion, fetal death, or low birthweight; Ali et al, ; Alsaif, Dabelah, Featherstone, & Robinson, ; Al‐Tawfiq & Memish, ; Elshamy & Ahmed, ; Giakoumelou et al, ; Gulsun, Aslan, Satici, & Gul, ; Kurdoglu et al, ; Mohammad, El Ghazaly, Zaalouk, Morsy, & El‐Ghazaly, ; Mujuni et al, ; Vilchez, Espinoza, D'Onadio, Saona, & Gotuzzo, ), arguing that brucellosis is a threat for pregnant women. Infection can also be transmitted to the fetus (congenital brucellosis), most probably through transplacental spreading (Alsaif, Dabelah, Girim, Featherstone, & Robinson, ; Aydin et al, ; Giannacopoulos, Eliopoulou, Ziambaras, & Papanastasiou, ; Glocwicz, Stonecipher, & Schulte, ; Koklu et al, ; Mesner et al, ; Poulou, Markou, Xipolitos, & Skandalakis, ; Vilchez et al, ), or to the neonate (neonatal brucellosis), upon exposure to maternal fluids during delivery (Carbajo‐Ferreira, Ochoa‐Sangrador, Canut‐Blasco, & Castaño‐García, ; Singer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It should, however, be mentioned that a prevalence as high as 58.1% was reported from a study which investigated the association of Brucella seropositivity with abortion for a group of 148 women with spontaneous abortions and 250 women with full‐term deliveries. The group of women with spontaneous abortions had a prevalence of 58.1%, while the group with full‐term deliveries had a prevalence of 26% (Mujuni et al., 2018). A different but also focused study on 250 abattoir workers and meat vendors in the city of Mwanza reported that 48.4% of them were Brucella seropositive (Mirambo et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on livestock and human brucellosis prevalence in Rwanda in the last decade (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) deliveries. The group of women with spontaneous abortions had a prevalence of 58.1%, while the group with full-term deliveries had a prevalence of 26% (Mujuni et al, 2018). A different but also focused study on 250 abattoir workers and meat vendors in the city of Mwanza reported that 48.4% of them were Brucella seropositive (Mirambo et al, 2018).…”
Section: Ta B L Ementioning
confidence: 98%